2011
DOI: 10.1002/j.2050-0416.2011.tb00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ITS PCR and RFLP for Differentiation and Identification of Brewing Yeast and Brewery ‘Wild’ Yeast Contaminants

Abstract: A reference library of ITS PCR/RFLP profiles was collated and augmented to evaluate its potential for routine identification of domestic brewing yeast and known 'wild' yeast contaminants associated with wort, beer and brewing processes. This library contains information on band sizes generated by restriction digestion of the ribosomal RNA-encoding DNA (rDNA) internal transcribed spacer (ITS) region consisting of the 5.8 rRNA gene and two flanking regions (ITS1 and ITS2) with the endonucleases CfoI, HaeIII, Hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 51 publications
7
50
0
1
Order By: Relevance
“…All the K. marxianus isolates have bands length at 240, 185, and 80 bp, but only 12 out of the 29 strains show the frequently reported K. marxianus profile (Esteve-Zarzoso et al, 1999; Bockelmann et al, 2008; Pham et al, 2011) with a band at 120 bp (from now on referred to as Group I), while the other 17 strains show a larger band, approximately of 140 bp (from now on referred to Group II).…”
Section: Resultsmentioning
confidence: 98%
“…All the K. marxianus isolates have bands length at 240, 185, and 80 bp, but only 12 out of the 29 strains show the frequently reported K. marxianus profile (Esteve-Zarzoso et al, 1999; Bockelmann et al, 2008; Pham et al, 2011) with a band at 120 bp (from now on referred to as Group I), while the other 17 strains show a larger band, approximately of 140 bp (from now on referred to Group II).…”
Section: Resultsmentioning
confidence: 98%
“…Molina et al (1992) found that the size of the PCR product with primers complementary to the ITS region in the species S. cerevisiae, S. bayanus and S. pastoriunus is approximately 850 bp, while the S. kluyveri (currently Lachancea kluyveri) provides a fragment of about 700 bp. Restriction analysis of the ITS region using enzymes has been performed to distinguish between species (Valente et al, 1996;Pham et al, 2011). Digestion of the PCR product by the HaeIII enzyme makes it possible to distinguish species within the genus Saccharomyces, but not between S. pastorianus and S. bayanus (McCullough et al, 1998).…”
Section: ■ ■ 3 Results and Discussionmentioning
confidence: 99%
“…In order to determine the identity of the isolates, the 5.8S rDNA and flanking ITS region was amplified by PCR and analysed by electrophoresis to determine amplified product size . PCR products were then digested with restriction enzymes Hha I (isoscizomer of Cfo I), Hae III and Hinf I. Digestion products were separated on 2% agarose gels, and band patterns were compared with published yeast RFLP databases . The results are shown in Table .…”
Section: Resultsmentioning
confidence: 99%